The Effectiveness of Self-Encouragement Training in Mental Health of Women with Addicted Spouses - Hosein Salimi Bajestani; parastoo farkooravand; j Younesi (Drug Control Headquarters, Research and Education Office, 2015)
Objective: This study aimed to examine the effectiveness of self-encouragement training in mental health of Tehran women with addicted husbands. Method: A quasi-experimental method along with pre-test/post-test and control group was used for this study. The sample consisted of 20 women with drug-dependent spouses (in Pak Andishan Rehab Clinic of Tehran) who were selected on a voluntary basis and, then, were randomly assigned to two 10-person experimental and control groups. The experimental group participated in 10 self-encouragement training sessions and, then, both groups were assessed by general health questionnaire. Results: The results of this study showed that training sessions had a significant impact on mental health. Conclusion: Self-encouragement training sessions can result in an increase in mental health.